Design and Performance Analysis of Permanent Magnet Claw Pole Machine with Hybrid Cores - Chengcheng Liu; Zheng Chao; Shaopeng Wang; Youhua Wang (CES Transactions on Electrical Machines and Systems, 2023)
Permanent magnet claw pole machine (PMCPM) is a special kind of transverse flux permanent magnet machine. Compared with other electrical machines, it has the advantages of high torque density and high efficiency for high speed operation. However, because of its complex irregular structure, the manufacturing process using silicon sheets is complicated. Soft magnetic composite material (SMC) is manufactured by powder metallurgy technology, which can produce various shapes of stator core structures, so it is easier to produce various irregular shapes of the stator core. However, the raw SMC material is relatively expensive, and the mechanical strength of SMC is weak. In this paper, a PMCPM with hybrid cores is proposed. With the adoption of hybrid silicon sheet - SMC cores and amorphous alloy - SMC cores, the torque ability of PMCPM can be improved greatly and it can have higher efficiency for more wide operation frequency. Meanwhile, its mechanical strength has been improved and it can be designed for high torque direct drive applications as it is a modular machine. Furthermore, three methods are proposed to reduce the additional eddy current loss which resulted from the employment of hybrid cores in PMCPM.